2017
DOI: 10.2174/1874364101711010011
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in Orbital Fractures

Abstract: Purpose:To determine whether prophylactic antibiotic use in patients with orbital fracture prevent orbital infection.Design:Retrospective cohort study.Participants:All patients diagnosed with orbital fracture between January 1, 2008 and March 1, 2014 at The George Washington University Hospital and Clinics.Main Outcome Measures:Development of orbital infection.Results:One hundred seventy-two patients with orbital fracture met our inclusion and exclusion criteria. No orbital infections were documented. Twenty s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Table summarizes the eight studies that were excluded from our meta‐analysis . None of the studies found a significant benefit of postoperative antibiotic prophylaxis in reducing infection rates.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table summarizes the eight studies that were excluded from our meta‐analysis . None of the studies found a significant benefit of postoperative antibiotic prophylaxis in reducing infection rates.…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies found a significant benefit of postoperative antibiotic prophylaxis in reducing infection rates. Reiss et al suggested that for low‐risk facial fracture patients, antibiotic prophylaxis may not be necessary . Amin et al found no significant difference in infection rates regardless of duration of postoperative antibiotic prophylaxis …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations